PEMBERDAYAAN KADER DALAM UPAYA PENCEGAHAN KOMPLIKASI HIPERTENSI PADA LANSIA PASCA BENCANA DI DESA GHEOGOMA KABUPATEN ENDE: - Sekunda, Maria S.; Bai, Marieta K. S.; Woga, Raimunda (Poltekkes Kemenkes Kupang, 2024)
Disasters can occur at any time and without knowing the time of occurrence. Some of the impacts of disasters that occur in life are damaged health facilities, lack of implementation of posyandu for the elderly and limited reach of health services, thereby increasing morbidity rates in the community, especially the elderly. One of the non-communicable diseases (NCDs) that often occurs in the elderly is hypertension. In the post-disaster period, elderly people who suffer from hypertension need to have their blood pressure monitored and controlled to prevent complications from hypertension. Hypertension is one of the main risk factors for global death and is estimated to cause 9.4% of world deaths annually (WHO, 2015). Cadre training in preventing post-disaster illnesses in the elderly is very important to minimize and reduce the risk of complications from hypertension in disaster victims. The aim of this community service activity is to control potential complications of hypertension in the elderly in the post-disaster period. The target of this community service activity is elderly posyandu cadres who live in Gheogoma Village, Ende District, Ende Regency. The method used in this activity is providing health education through counseling, mentoring and training of cadres, training in checking blood pressure. The location and time of the activity will be held on 12-13 June 2023 in Gheogoma Village, Ende District, Ende Regency. The results of the activity showed that 80 percent of the cadres had good knowledge and of the 12 participants, 11 cadres were able to measure blood pressure well, and 3 cadres were adequate at measuring blood pressure. It is hoped that cadres will continue to be active in measuring blood pressure and utilize the skills they have by carrying out blood pressure checks for Gheoghoma village residents who need them